Financial Flexibility and Financial Constraints: Firm-Level Empirical Evidence - Elryanti; Satrio, Arif Budi (Relevance: Journal of Management and Business, 2025)
Increasing market competition means that business sustainability depends not only on innovation capacity but also on adaptive financial strategies. One crucial issue related to this strategy is financial flexibility, which enables companies to manage their liquidity and debt capacity effectively in response to funding challenges. This study advances the literature by examining 144 firms (2020-2024) using multidimensional financial flexibility proxies combined with a validated financial constraints index, thereby generating new evidence from Indonesia's institutional environment. Fixed effects, random effects, and the two-step system generalized method of moments analyses were conducted to ensure robustness. Empirical results indicate that financial flexibility has a significant negative impact on financial constraints. These results confirm the crucial role of internal mechanisms in reducing dependence on external funding. This study validates financial flexibility as a strategic instrument in mitigating market imperfections and providing practical insights for companies and regulators in emerging markets.